Analysis Application of Altman (Z-Score) Method and Springate (S-Score) Method to Assess Financial Distress Potential at PT Anugerah - Kadek Mega Ciptaningsih; I W Karman; Istiarto Istiarto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
The emergence of potential financial distress is an early indication of a decline in the company's financial condition. The purpose of this research is to determine the potential of financial distress at PT Anugerah, so that it will help management anticipate the potential financial distress in the company. In this research, the assessment of financial distress potential uses the Altman (Z-score) method and Springate (S-score) method. The type of data in this research is quantitative and qualitative sourced from secondary data and obtained through interviews, documentation, and observation. The data analysis technique used is a qualitative/descriptive analysis technique. The results of research study are the financial distress potential of PT Anugerah by using the Altman (Z-score) method in 2016-2019 shows PT Anugerah is in a non-financial distress condition, because the score is in the condition of Z’’> 2.6. Furthermore, PT Anugerah financial distress potential using the Springate (S-score) method in 2016-2019 shows that PT Anugerah is in a non-financial distress condition, because the score is at S > 0.862.